Time management for department chairs - Hansen, Christian K. (San Francisco, CA : Jossey-Bass, 2011)
'In this concise, highly practical book, Christian Hansen draws on his years of research on time management for department chairs. He shows department chairs how to set priorities, create a time budget and log, harness technology to assist in time management, and make self-care a priority. As a handy paperback, this book is designed to be an easy-to-access resource that will not only make department chairs' jobs easier but will also help them to manage stress and prevent burnout.'--
Includes bibliographical references (p. 131-133) and index.
Keywords: College department heads; Universities and colleges -- Administration; Time management; EDUCATION / Administration / General